The little critters matter too: analysing social media data to inform insect conservation efforts - Tan, Belle Mei Yi (Nanyang Technological University, 2023)
Insects are important to the world’s ecosystems, forming the foundation of most food webs and providing various ecosystem functions such as pollination, nutrient cycling, and pest control. However, recent publications have highlighted a significant decline in insect populations, largely due to human activities. Although these data on insect declines have been criticised as alarmist and unrepresentative of the global state of insect declines, such trends nonetheless raise causes for concern. Some main concerns are that there remains a lack of insect research in important locations such as Southeast Asia, and that there are certain taxonomic biases in studies of biodiversity conservation that place insects at a disadvantage. As such, alternative sources of data, such as social media, may help to create a more representative global picture of biodiversity conservation. This paper explored biodiversity conservation data on social media to provide an overview of biodiversity conservation efforts and its associated public perceptions, particularly with respect to insect conservation efforts vis-à-vis other taxonomic groups. In total, two datasets were collected – the first using the “#conservation” search term on Facebook and Twitter, and the second from the Facebook, Instagram, and Twitter pages of selected biodiversity conservation organisations. Analyses revealed that insects remain significantly under-represented in biodiversity conservation content on social media and that insect-related content is biased towards bees and butterflies. On the bright side, insect representation increased from 0% in 2008 to 3.08% in 2022 and insect-related content is largely positively presented by content creators and well received by the public.